Influence on Mechanical Characteristics of Thickness of Layers in MoN/CrN Multilayer Coatings, Deposited Under the Influence of Negative Bias Potential - V.М. Beresnev; O.V. Sobol´; А.V. Stolbovoy; S.V. Lytovchenko; D.А. Kolesnikov; U.S. Nyemchenko; А.А. Meylehov; А.А. Postelnyk (Журнал нано- та електронної фізики)
A complex study of the influence of thickness of layers of multilayer composition MoN/CrN on phase and structure state and mechanical properties of the coatings during applying constant negative Ub has been held using structure engineering method. It was found that mixing in interboundary areas of the layers at high Ub = – 150 V leads to sharp decrease of mechanical properties at thickness of layers h ≤ 40 nm. The highest hardness of 39.8 GPa and abrasive strength for LC5 = 145 N was reached at h ≈ 12 nm at applying small Ub = – 20 V.